HUBUNGAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN PRODUKTIVITAS KERJA KARYAWAN - Muhammad Riduan; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Safety and healthy works means that the planning process and controlling situation that works accident according the preparing standard procedure that can be the guidence in working. The employees are the people working in under organisation with one system activity that commounding from the some people with coorporation to reaching the goal, one of the parrameter’s personal succes team or the organisation placed in productivity. if the productivity is low it’s called NO or less succes.The location of this research will doing in PT. Geliga Bagan Riau addressed in jalan Dusun Bhakti komplek bagan permai 55 kecamatan bagan sinembah kabupaten rokan hilir provinsi riau. The aims of this research is to determine the corralation safety and healthy works by the productivity.The method that used in this research is analyze instrument corralation spearman by the SPSS programe, in order to the sample that using in this reserach is the employee position PT. Geliga Bagan Riau and as the source of information is the Manager. To determine the sample used the slovin formula, and technic to take the sample is simple random sampling. The way to take the data through the interview, observation, dan quesioner.Based on the data analyze contain of the validity test, reabilitas, and corralation spearman test rank, the strategy to do safety and healthyworks in this research contain of the five (5) component that is the condition and employee condition,works environment, protecting the employee, work place, mechine and the equipment, works attitude, skills, and the corralation between works environment, management of the productivity and effciency labour. Safety and healthy works (K3) have the corralation by the works productivity with coofisien value about 0,646 with value of t counts bigger than t table (7,395 > 2,007).Key words : safethy and healthy work, productivity